1985
DOI: 10.1159/000173856
|View full text |Cite
|
Sign up to set email alerts
|

Ergometry in the Assessment of Arterial Hypertension

Abstract: The blood pressure behavior during and after ergometric exercise was investigated in 552 males in order to clarify if this standardized procedure is suitable for differentiating between normotensive subjects and hypertensive patients. Patients suffering from mild hypertension showed significantly (p < 0.001) higher blood pressures (213 ± 22/116 ± 11 mm Hg) at 100 W and after loading than age-matched normotensives (188 ± 14/92 ± 9 mm Hg) but significantly (p < 0.001) lower values than hypertensives with stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In contrast, DBP remains unchanged or shows only a slight increase as a consequence of metabolic vasodilatation of the peripheral vessels. 17 However, some researchers 11,17,18 have observed a significant rise in DBP even in normotensive subjects, suggesting an increased resting peripheral vascular resistance 11,19 and impaired capacity for exercise-induced vasodilation. 20,21 This hemodynamic pattern can be explained by a hyperreactivity of the sympathetic nerves and an increased vascular response to adrenergic stimulation or by a thickening of the arteriolar wall that alters its ability to respond to vasoconstrictor stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, DBP remains unchanged or shows only a slight increase as a consequence of metabolic vasodilatation of the peripheral vessels. 17 However, some researchers 11,17,18 have observed a significant rise in DBP even in normotensive subjects, suggesting an increased resting peripheral vascular resistance 11,19 and impaired capacity for exercise-induced vasodilation. 20,21 This hemodynamic pattern can be explained by a hyperreactivity of the sympathetic nerves and an increased vascular response to adrenergic stimulation or by a thickening of the arteriolar wall that alters its ability to respond to vasoconstrictor stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…22 Conversely, statistically significant differences appear in indirect DBP readings measured especially during maximal exercise 16,22,23 because maximal ergometric work requires isometric muscle contractions, which produce a marked increase in total peripheral resistance. 11,17,18 However, it has been demonstrated that direct and indirect measurements of DBP satisfactorily correlate below the workload of mild or moderate exercise. 17,18,22,23 Furthermore, several studies have shown that endurance-trained persons are more likely to exhibit significantly higher SBP increases during maximal exercise than untrained persons, despite their reduced risk for developing hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown in the literature that diastolic BP response to exercise is mediated by the vasodilation capacity of peripheral vessels and the consequent reduction in peripheral vascular resistance 25 . Ordinarily, diastolic BP remain constant or show small increases during submaximal or maximal aerobic exercise 22,26 . In this study, diastolic BP increased significantly only after exercise in the postprandial condition.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with coronary heart disease, maximal systolic blood pressure was shown to be significantly related to the severity of coronary artery disease (10). The blood pressure response to exercise has been used in the assessment of hypertension (7,14) or to detect persons at risk for future hypertension (4,2 1). Considerable variations in blood pressure have been reported (2).…”
Section: Introductionmentioning
confidence: 99%